Aplikasi Mudah-Alih Android eSmart Passenger (Keretapi Tanah Melayu Berhad) - Saifuddin, Mas Hazimah; Mohd Yunus, Mohd Amin; Huda A Majid, (Applied Information Technology And Computer Science, 2021)
eSmart Passenger (Train Tanah Melayu Berhad) android mobile application is a payment application that uses QR code technology for payment products for rail services in the state. The current system, the Integrated Ticket System (KITS), has offered an online purchasing system . It has several issues that arise one of which is the online ticket purchase system which is often problematic and not user friendly and sometimes inaccessible especially during the festive season. By looking at these weaknesses then the eSmart Passenger Application will be developed with the aim of helping users who use train services in terms of purchasing products such as travel tickets. The application also facilitates the management of passenger itineraries to be more organized and save time and energy with the help of an alarm system. The main module of this application consists of registration module, information data update, travel alarm notification, ticket payment, top -up in eSmart Pay, route map as well as payment transaction report generation module. The methodology used for this application is the Prototype model. In addition, the programming language used in the development of this application is Java and Hypertext Preprocessor (PHP) while Firebase as a system database as well as Android Studio editing software. This application was created for convenience, orderliness and to ensure the safety of users by utilizing QR code technology which is expected to overcome various problems faced by the existing system, namely the Integrated Ticket System (KITS).